A Putative Oral Vaccine based on Live Lactococci Expressing the Surface Glycoproteins Respiratory Syncytial Virus. - Lim, Erin Swee Hua (2010)
Although 50 years have elapsed since the discovery of respiratory syncytial virus (RSV), it remains the primary cause of lower respiratory tract disease in children worldwide without a licensed vaccine which is of utmost priority. On the other hand, bacterial surface display has, in the last two decades emerged as an exciting, novel method for the anchoring of proteins for therapeutic and industrial purposes. The idea for this project was birthed by combining both these developments to meet the need for an effective RSV vaccine. Gram-positive bacteria such as Lactococcus lactis is attractive for use as a vaccine delivery vehicle as the absence of an outer membrane allows direct exposure of bioactive molecules to the extracellular compartment. L. lactis is also safe for oral administration due to its generally regarded as safe (GRAS) status. Live microbial vectors are more efficient than killed vectors at stimulating a secretory response to a recombinant antigen because of active multiplication. It is with these in mind that this work was developed. Domains from the genes of the F and G glycoproteins, of RSV which are essential target antigens were selected and cloned into an Escherichia coli expression vector, pRSETC. The proteins expressing the domains were expressed and purified. Polyclonal antibodies in rabbits, denoted anti-rF and anti-rG, were raised against them. The raised polyclonal anti-rF, could recognize the full-length F protein from the native virus whereas commercially acquired polyclonal anti-RSV was able to recognize the unglycosylated rF protein domain from E. coli. Other workers have proven the immunogenicity of the selected G domain and ascertained that glycosylation is not necessary. Upon confirmation that both these domains were suitably immunogenic, bacterial expression cassettes were constructed for surface display expression in L. lactis. The L. lactis bacterial expression cassette, from the 5’ downstream to the 3’, comprises a signal peptide of the USP45, the F or G domains as the antigenic protein and the cA domains of the cell wall hydrolase AcmA, ranging from one to three repeats. These repeats were necessary to investigate the effect of the number of repeats on the surface display and expression on L. lactis. Confirmation of surface display was carried out by extraction of the cell wall fraction of L. lactis and detection of the F and G domains by immunoblotting. Fluorescence microscopy confirmed the presence of these domains on the cell surface. Whole-cell ELISA indicated that an increase in the number of cA domain repeats increases the occurrence of surface display for the G domain. However, an increase in the number of cA domain repeats decreases the occurrence of surface display for the F domain. This could be attributed to the differences in the size of both domains. Recombinant Lactococcus displaying the F and G glycoproteins by fusion to three repeats of the cA domain, named pNZ-UFA3 and pNZ-UGA3 (refer Tab 2), were tested in a mouse model and the immune responses determined. The results obtained indicate that L. lactis harbouring pNZ-UFA3 and pNZ-UGA3 are suitable vaccines against RSV, as they are able to stimulate balanced Th1/Th2 responses with a more biased Th1 immune response.